Cognitive behavioural interventions with pupils with learning disabilities: an evaluation of the impact of the Feelings Detectives Programme on anxiety - Holderness, Helen (2020)
Cognitive Behavioural Interventions have been shown to be effective in reducing the anxiety of typically developing children and adults with learning disabilities (LD). Research into the effectiveness of cognitive behavioural approaches to treat anxiety in children and young people (CYP) with LD is in its infancy. The aim of this study was to investigate the impact of a recently developed cognitive behavioural programme called Feelings Detectives on the anxiety of six 15-year-old pupils with LD, who attend a school for CYP with complex needs.